The Roles of Cycloxygenase and Endothelial Derived Hyperpolarizing Factors in Bradykinin-Induced Aortic Relaxation - Omar, Ali Z.; Maulood, Ismail M. (Science Journal of University of Zakho, 2017)
The present study is designed to investigate the roles of cycloxygenase (COX) and endothelial derived hyperpolarizing factors (EDHF) pathways in bradykinin (BK)-induced aortic relaxation. Here, isolated aortic rings pre-incubated with different ion channel blockers which are; inward rectifier potassium channel blocker (barium chloride; BaCl2), calcium activated Potassium (KCa+2) channel blocker (tetraethylammonium; TEA), cytochrome P450 inhibitor, clotrimazole and cycloxygenase inhibitor and indomethacin. In BaCl2, Emax tended to decrease significantly with significant change of PIC50. TEA pre-incubation markedly shifted DRC of BK to the left side and it significantly reduced PIC50. Indomethacin significantly lowered the PIC50 of BK, but it shifted the DRC of BK to the left. The results suggested that BK relaxes aortic smooth muscle particularly via the enhancement of cycloxygenase and epoxygenase enzymes as well as through opening Kir and KCa+2channels.